Penggunaan Gyakusetsu No Setsuzokushi Dalam Novel Tobu Ga Gotoku Karya Ryoutarou Shiba - Siska Nusantari, Ni Made; Rauh Artana, I Nyoman; Luhur Wedayanti, Ni Putu (Humanis; Volume 16. No. 3. September 2016, 2016)
The research entitled “The usage of Gyakusetsu no Setsuzokushi in Tobu ga Gotoku Novel by Ryoutarou Shiba”. The theories used for analyzing are syntax theory by Verhaar (2012) and semantics theory by Pateda (2001). As the result, gyakusetsu no setsuzokushi daga is connected with noun and used when expresses that is contrasted with what is expressed in the previous sentence. Then, gyakusetsu no setsuzokushi shikashi is connected with the first clause and first sentence. This conjunction used when the sentence is oposite and used when disagree with other people opinion. Gyakusetsu no setsuzokushi ga is connected with first clause and first sentence. This conjunction is used when using to connect the oposite sentence, it’s using to sort event and used to describe expression. Setsuzokushi to wa ie connected with first clause and first sentence. This conjunction used to connected two oposite sentence, and used when to expect something. Then, gyakusetsu no setszokushi tadashi, mottomo and tokoroga is connected with first sentence. Setsuzokushi tadashi is used when expresses that is contrasted with previous sentence. Gyakusetsu no setsuzokushi mottomo used to add a comment indicating that what the people has just expressed is not sufficient. Then, tokoroga which is used to present what in fact the case when something else was expected.